Gap Analysis in Implementing IFRS S1 and IFRS S2: A Case Study at Bank X in Indonesia - Mela Amelia; Chaerul Djakman (International Journal of Economics Development Research (IJEDR), 2024)
On June 2023, the ISSB published two sustainability disclosure standards IFRS S1 and IFRS S2. This study aims to analyze the disclosure of climate-related reports based on IFRS S1 and S2 standards. Four primary aspect Governance, Strategy, Risk Management, and Metrics and Targets need to be disclosed based on IFRS S1 and S2. The author identified a total of 29 main criteria that need to be disclosed. This study used qualitative research approach through literature studies, documents, and interviews. This research was conducted in one of the Indonesian companies in the banking sector. The findings demonstrated that, of the four primary aspect, Governance (9/9) has been evaluated in compliance with IFRS S1 and S2, but due to various stages of the development process, Strategy (8/12), Risk Management (1/3), and Metrics and Targets (3/5) have not yet been completely disclosed. Primarily in part to issues with technology and data, such as merging climate risk to "transverse risk" in the scenario analysis process, the company has not been able to quantitatively integrate climate-related risks and opportunities with financial performance and financial position.